Recent advances in smart manufacturing and materials select proceedings of ICEM 2020 - Agrawal, Rajeev; Jain, Jinesh Kumar; Yadav, Vinod Singh; Manupati, Vijaya Kumar; Varela, Leonilde (Lecture Notes in Mechanical Engineering, 2021)
This book presents select proceedings of the International Conference on Evolution in Manufacturing (ICEM 2020), and examines a range of areas including internet-of-things for cyber manufacturing, data analytics for manufacturing systems and processes and materials. The topics covered include modeling simulation and decision making in cyber physical systems for supporting engineering and production management, innovative approach in materials development, biomaterial applications, and advancement in manufacturing and material technologies. The book also discusses sustainability in manufacturing and supply chain management including circular economy. The book will be a valuable reference for beginners, researchers, and professionals interested in smart manufacturing in engineering, production management and materials technology.